Ethnopedagogy Based On Pancawaluya Values In Character Development In Middle Schools - Vironita, Evi; Penisiani, Dian (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Character education in secondary schools can no longer be understood solely as a process of instilling universal values, especially when students live in a constantly changing social and cultural landscape. In the context of globalization, the expansion of digital culture, and the dynamics of adolescent identity, character education approaches that are detached from students’ cultural realities tend to lose their relevance. This article aims to critically examine Pancawaluya-based ethnopedagogy as an alternative approach to character development in secondary schools. This research uses a literature review method by analytically examining scientific literature discussing ethnopedagogy, character education, and Sundanese cultural values. The results of the study indicate that ethnopedagogy functions not only as a culture-based learning approach but also as an epistemological critique of ahistorical and normative models of character education. Within this framework, Pancawaluya, through its values ​​of cageur, bageur, bener, pinter, and singer, is understood as a holistic value system directly related to the real-life issues of high school adolescents, such as identity formation, social empathy, discipline, and creativity. The discussion reveals a gap between the philosophical depth of Pancawaluya values ​​​​and the practice of character education in schools, which still tends to be symbolic and fragmented. This article concludes that the integration of ethnopedagogy and Pancawaluya values ​​needs to be positioned as a contextual and sustainable reconstruction of character education paradigms, and provides theoretical and practical implications for the development of local culture-based character education in high schools.